Stability of wheat genotypes for grain yield using the GGE Biplot methodology - Marchioro, Volmir Sergio; Reffatti Bastiani, Ricardo; Klein, Luís Antônio; Mühl Ignacio, Évelyn Clarissa; Mäger Kittlaus, Ketlyn; Ribeiro Feldens, Marlon (Revista Ceres, 2025)
Wheat plays an important role in global agriculture, being one of the most widely cultivated cereals. Wheat cultivation in each region depends on the stability of grain yield in the given environment. The objective of this study was to identify the most productive and stable genotypes over three years of cultivation in the municipality of Frederico Westphalen, using GGE Biplot analysis. Twelve wheat genotypes were cultivated in a randomized complete block design, with three replicates over three years from 2019 to 2021. The experimental units consisted of six 4-meter rows, spaced 0.17 m apart. Grain yield was measured 3 meters from the four central rows. The data obtained was subjected to analysis of variance, which verified interactions between genotypes and years, and then performed GGE Biplot analysis. The grain yield of the wheat genotypes was influenced by the environmental conditions during the three years of cultivation. The genotypes UFSMFW 1-07 and USFMFW 1-04 were more productive in specific years, with the best performance for grain yield and stability being that of the genotype UFSMFW 1-08.